2022
DOI: 10.1016/j.jad.2021.12.114
|View full text |Cite
|
Sign up to set email alerts
|

The effects of perceived psychological, educational, and financial impact of COVID-19 pandemic on Greek university students’ satisfaction with life through Mental Health

Abstract: Background The purpose of this study was to provide an operating mechanism for understanding the effects of COVID-19′s on satisfaction with life, subject to students’ general mental health Methods A sample of 1653 Greek speaking university students (72.4% females, 65.3% undergraduate, M age=26.1) completed an online survey including measures for perceived psychological, academic, and financial impact of the COVID-19 pandemic, general mental health and satisfaction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 52 publications
1
35
0
1
Order By: Relevance
“…The education sector is highly vulnerable to a pandemic. The education disparities ( Jiang et al, 2021 ) and financial challenges of students ( Galanza et al, 2021 ; Li et al, 2021 ; Schröpfer et al, 2021 ; Kokkinos et al, 2022 ) are important issues to be addressed and institutional support ( Poma et al, 2021 ; Schmits et al, 2021 ) and mentoring ( Lee et al, 2021 ) can be a good move in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The education sector is highly vulnerable to a pandemic. The education disparities ( Jiang et al, 2021 ) and financial challenges of students ( Galanza et al, 2021 ; Li et al, 2021 ; Schröpfer et al, 2021 ; Kokkinos et al, 2022 ) are important issues to be addressed and institutional support ( Poma et al, 2021 ; Schmits et al, 2021 ) and mentoring ( Lee et al, 2021 ) can be a good move in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, educational disparities can also happen due to financial distress during pandemic ( Jiang et al, 2021 ). Students are another vulnerable community to financial stress during COVID-19 ( Galanza et al, 2021 ; Schröpfer et al, 2021 ; Kokkinos et al, 2022 ) and impacted by the economic instability and psychological issues ( Li et al, 2021 ); old-aged community ( Heid et al, 2021 ; Kivi et al, 2021 ). However, there are contradicting findings that the dental students are least concerned about their financial status during pandemic ( Poma et al, 2021 ).…”
Section: Thematic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Based on what has been reported in scientific literature, life satisfaction among higher education students has changed during the COVID-19 health emergency due to the impact of the disease (Rogowska et al, 2021), especially given its strong relationship with quality of life and personal goals (Huang et al, 2022), which have been affected by students' concern about contracting the disease (Hossain et al, 2021), new variants (Carranza et al, 2022), precarious health systems (Knaul et al, 2021), financial impact (Kokkinos et al, 2022), and others. Authors such as Lei et al (2020) report that being a student in COVID-19 times is a risk factor for mental health conditions compared with other age groups.…”
Section: Life Satisfactionmentioning
confidence: 99%
“…For example, a study conducted in USA found that during the pandemic high levels of depression were associated with difficulties in focusing on academic work ( 10 ). Other findings demonstrated that mental health distress was correlated to a perceived poor academic performance caused by SARS-CoV-2 ( 11 ).…”
Section: Introductionmentioning
confidence: 99%